Twelfth night - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. Simply Shakespeare., 2002)
Presents the original text of Shakespeare's play side by side with a modern version, with discussion questions, role-playing scenarios, and other study activities. The Bard's original poetic phrases are printed side-by-side and line-by-line with the modern translation on each facing page. While Shakespeare's immortal plays have endured, the English language has changed -- which is why today's students often find Shakespeare's idiom difficult to comprehend.